2019
DOI: 10.18502/jchr.v8i1.559
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and Prioritizing Factors Affecting Health Literacy in University Students of Yazd Using Artificial Neural Network Technique

Abstract: Introduction: Current university students are potential and actual parents of future generations. The level of their health literacy affects health and health literacy level of future generations. Therefore, the purpose of the present study was investigating and prioritizing the factors affecting the health literacy of students in Yazd (a city in central Iran) using an artificial neural network technique. Methods: This study was cross-sectional and descriptive and it was conducted on 400 university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the present study, although the relationship between age and health literacy was not statistically significant, the results showed that with increasing age, the desirability of health literacy in students increases. In a study conducted on students in Yazd City, Iran the results showed the variables of age and educational level as factors affecting health literacy [22]. The results of a study on the students of Farhangian University also showed that the level of health literacy increases with the older age [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, although the relationship between age and health literacy was not statistically significant, the results showed that with increasing age, the desirability of health literacy in students increases. In a study conducted on students in Yazd City, Iran the results showed the variables of age and educational level as factors affecting health literacy [22]. The results of a study on the students of Farhangian University also showed that the level of health literacy increases with the older age [17].…”
Section: Discussionmentioning
confidence: 99%
“…The first type is focused on measuring the level of adherence to literacy practices according to specific factors for the purpose of identifying and improving weaknesses in a specific healthcare institution [43] or in a group of institutions [44][45][46]. The second type is focused on measuring the relative importance of the areas and indicators of applying literacy practices for the purpose of determining the most important or most appropriate factors for the institution or a specific health sector [47]. However, there is an applied research gap around the third and fourth types.…”
Section: E Assessment Of the Organizational Health Literacymentioning
confidence: 99%